2015
DOI: 10.1111/hae.12743
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of bone loss using quantitative ultrasound in a blood‐induced arthritis rabbit model

Abstract: In conclusion, QUS' acceptable reliability, its responsiveness to growth-related changes and its ability to discriminate injected and non-injected joints make this technique a plausible candidate as a diagnostic tool for osteoporosis in the paediatric haemophilic population if these results are confirmed upon animal-human translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Application of in vivo US in animal models of HA is a new area of investigation, with only few publications [15][16][17]. In the present study, US revealed joint pathology 14 days after induction of one or two joint bleeds, including oedema (soft tissue swelling), ligament swelling and disruption of the fat pad.…”
Section: Discussionmentioning
confidence: 48%
“…Application of in vivo US in animal models of HA is a new area of investigation, with only few publications [15][16][17]. In the present study, US revealed joint pathology 14 days after induction of one or two joint bleeds, including oedema (soft tissue swelling), ligament swelling and disruption of the fat pad.…”
Section: Discussionmentioning
confidence: 48%
“…The following observed results also indicated pathogenesis similar to human RA. Thus, the choice of a rabbit model is suitable for research [ 23 ]. The lower price, suitable feeding, and molding were other factors influencing our experimental methods.…”
Section: Discussionmentioning
confidence: 99%
“…As described in previous studies [18, 28, 34, 35], for 8 weeks, intra-articular autologous blood injections were administered twice per week to create mild arthropathy in both knees of each rabbit in Group A. Intra-articular autologous blood injections were administered twice per week for 16 weeks to create severe arthropathy in both knees of each rabbit in Groups B and C (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%